COMPARISON EVALUATION OF FREQUENCY RESPONSE FUNCTION MEASUREMENT RESULT USING MULTIPLEXING DATA ACQUISITION DEVICE PCI-6281 AND MULTI CHANNEL SIMULTANEOUS DATA ACQUISITION DEVICE MSA HP3566A - William
Frequency Response Function is a comparison function between response and excitation force which is presented in frequency domain, where the measurement of response and excitation force must be done simultaneously. ITB Dynamic Laboratory has developed softwares for FRF measurement using multiplexing data acquisition device and multi channel simultaneous data acquisition. Then, a research to see effects in using both of data acqusition devices in FRF measurement is needed. There were two softwares which is developed to control multiplexing data acquisition card PCI-6281 in this research. Each softwares can be used to do FRF measurement with impuls resopnse method and swept sine method. Those softwares were developed using LabVIEW 7.1 programming language, specific modul Sound and Vibration Toolkit 3.1, and device driver NI-DAQmx. In this research, FRF measurement was done with a T Plate and a simply supported beam structures using the developed softwares and MSA HP3566A, referenced data acquisition device. The developed softwares gave a wrong FRF measurement result since there was no anti-aliasing filter device in PCI-6281. The increased acquisition sampling rate returned small error in natural frequency reading and big error in the others FRF measurement unit reading.